Shoreline Stability Analysis At Merah Putih Beach, Bangkalan Regency - Dyah Ambarwati Rieke; Dwi Siswanto Aries (BIO Web of Conferences)
Shorelines serve as a key indicator in monitoring environmental changes in coastal areas. Shorelines can change over various time periods, triggering coastal abrasion or accretion which can be detrimental. Therefore, it is necessary to conduct research on shoreline changes to minimize the losses that occur. The main objective of this study is to estimate abrasion based on Net Shoreline Movement, Endpoint Rate, and Shoreline Change Envelope. The quantitative approach utilizes remote sensing technology using the Normalized Difference Water Index algorithm, while the statistical approach uses data analysis obtained from the Digital Shoreline Analysis System method. This research was analyzed using Landsat 8 satellite images over a 12-year period (2013-2024). The results showed that shoreline changes at Merah Putih Beach, Bangkalan Regency during the 2013-2024 period indicated abrasion with an average shoreline distance of 14.99 meters and with an average rate of 1.37 m / year. According to the classification of the coastline in DSAS statistics, the two segments with a value of 0.511 meters / year and -0.768 meters / year are included in the moderate abrasion category. So that the beach during the 12-year period experienced a stable condition with a significant beach dynamics profile.